THE CORRELATION AMONG THE ELEVENTH GRADE STUDENTS’ SELFCONFIDENCE, MOTIVATION AND SPEAKING ACHIEVEMENT AT PGRI SENIOR HIGH SCHOOL 2 OF PALEMBANG - Ike Yustanti (ELTE Journal (English Languange Teaching and Education), 2019)
The objectives of this study were to find out whether or not: 1) there was a significant correlation between the eleventh grade students’ self- confidence and speaking achievement at PGRI Senior High School 2 of Palembang; (2) there was a significant correlation between the eleventh grade students’ motivation and speaking achievement at PGRI Senior High School 2 of Palembang; (3) there was a significant correlation between the eleventh grade students’ self-confidence and motivation simultaneously and speaking achievement at PGRI Senior High School 2 of Palembang. This study was correlation researches with the population were 324 students. The samples for this study were 30 students (XI.IPA 2) taken through convenience sampling technique. Data were collected through questionnaires and test. Then, they were analyzed by using correlation analysis and multiple regression analysis. Findings show that: 1) there was significant correlation between the eleventh grade students’ self- confidence and speaking achievement at PGRI Senior High School 2 of Palembang; 2) there was significant correlation between the eleventh grade students’ motivation and speaking achievement at PGRI Senior High School 2 ofPalembang; 3) there was significant correlation between the eleventh grade students’ selfconfidence and motivation simultaneously and speaking achievement at PGRI Senior High School 2 of Palembang.Keywords: Self-Confidence, Motivation, Speaking Achievement